AB0036 Analysis of genetic polymorphisms in folate pathway affecting the efficacy of methotrexate in japanese patients with rheumatoid arthritis. (23rd January 2014) - Tazoe, Y.; Hayashi, H.; Tsuboi, S.; Morishita, M.; Arai, T.; Ohshima, M.; Matsuyama, T.; Kosuge, K.; Yamada, H.; Tsuji, D.; Inoue, K.; Itoh, K.
Abstract : Background: Low-dose methotrexate (MTX) is an anchor drug in the medication of rheumatoid arthritis (RA). However, MTX exhibited large inter-individual and inter-ethnic differences in the dose required for its anti-inflammatory effect. In order to maintain the low disease activity, there are also the patients who needs increase in dose of MTX, and who needs co-administration of biologic disease modifying anti-rheumatic drugs (bDMARDs). If there is a marker for predicting the effect of MTX, it will become possible to increase the dose of MTX or to prescribe bDMARDs for the patient at an early stage. Objectives: The present study examined genetic polymorphisms related to folate metabolism pathway in RA patients, with the intention of building evidence for implementing individualized drug therapy with MTX. Methods: Among Japanese patients who gave written consent under treatment at the Department of Rheumatology at Shizuoka Kousei Hospital, the present study examined a patient group with an unsatisfactory response to MTX and undergoing concomitant treatment with bDMARDs (bDMARDs concomitant group) and a patient group who had a stable response to MTX. We used DAS28 as an index for disease activity. To analyze genetic polymorphisms involved in folate metabolism pathway, we used a PCR-RFLP method and a direct sequencing method. The present study was conducted with the approval of the ethics committees of each related organization. Results: Eighty-nine patients were treated with MTX alone. MTX and bDMARDs were co-administered to 81 patients because of the insufficient efficacy of MTX (bDMARDs concomitant group). The results of a multivariate analysis using the concomitant of bDMARDs as the objective variable revealed a significant association between age and the G80A polymorphism of the reduced folate carrier 1 gene ( RFC1 ), as an explanatory variable (p=0.0018). Conclusions: DAS28 values showed no significant difference between the bDMARDs concomitant group and the MTX group, and both groups are thought to have achieved a therapeutic effect with the same degree of stability. Compared to patients with the A allele, patients with the G allele had less intracellular MTX uptake and therefore had poor efficacy; a greater number of them were found to be bDMARDs concomitant cases. The results of the present study suggest the possibility that the RFC1 G80A polymorphism may be a useful marker for predicting MTX efficacy in Japanese patients with RA. Disclosure of Interest: None Declared